CIVIL SOCIETY AND THE SOCIAL SCIENCES: EXAMINING POWER RELATIONS IN MODERN RUSSIA - Dmitry Sergeyevich Petrov; Yuri Aleksandrovich Smirnov; Mikael Korhonen (International Journal of Education and Social Science Studies, 2025)
This paper examines the intricate relationship between civil society and the social sciences in the context of modern Russia, where increasing authoritarianism has reshaped the boundaries of public discourse, academic inquiry, and civic engagement. Drawing on interdisciplinary approaches and qualitative analysis, the study explores how both civil society actors and social scientists navigate state-imposed restrictions while maintaining critical roles in resisting dominant power structures. The findings reveal that Russian civil society, although heavily constrained by legal and institutional pressures—such as the “foreign agent” and “undesirable organizations” laws—continues to adapt through decentralized, grassroots strategies, digital platforms, and symbolic resistance. In parallel, the social sciences face growing political interference, with state efforts to instrumentalize academic research and suppress critical perspectives. Nevertheless, many scholars pursue intellectual resistance through independent networks, international collaboration, and nuanced critique. The interplay between these two domains demonstrates a dual dynamic of collaboration and shared vulnerability. Civil society relies on scholarly knowledge to legitimize its claims and strategies, while the social sciences benefit from civic actors' empirical insights and lived experiences. Despite repression, this mutual relationship fosters innovation, resilience, and the continued production of critical knowledge in an increasingly hostile environment. This paper concludes that the relationship between civil society and the social sciences in Russia not only reflects broader struggles over power and autonomy, but also illuminates the enduring potential for democratic agency, even under authoritarian rule. Understanding this interplay is crucial for comprehending the sociopolitical dynamics of resistance and intellectual freedom in contemporary Russia.